Comportamento novo: uma análise do efeito da saliência de estímulos sobre respostas de resolução de problemas por meio da interconexão de repertório - Almeida, Carlos Vinícius Dias de (2024)
Investigating control variables for the observation response involved in the problem-solving repertoire is relevant to understanding the properties of stimuli that enhance the density or immediate access to reinforcement contributing to the delivery of target responses. Dinsmoor et al. (1983) analyze two factors in relation to stimuli that can interfere with observation responses: salience which they described as “the magnitude of the difference between each of the discriminative stimuli and its background stimulation” (p. 254), and the discrepancy he described as the magnitude of the difference between two stimuli" (p. 254). Thus, the present study investigated the influence of stimulus salience on the problem-solving response in an Insight task with four Wistar albino rats (Rattus Norvegicus ) males, experimentally naïve, around 4 months old, with 80% of their body weight, the following phases of the procedure proposed by Ferreira (2008) were adopted: (1) insight pre-test, (2) drinking fountain training, ( 3) impulse training, (4) intermediate test, (5) climb and pull training, (6) brute force response extinction, (7) response strengthening and (8) final insight test, and additional phases of (9) post-training and (10) post-test, manipulating the salience of the stimuli as proposed by Rossger (2011) in which two subjects were exposed to salient stimuli and two to transparent stimuli. The results indicate that subjects who underwent training with salient stimuli needed fewer sessions to reach phase change criteria, and that throughout the training sessions they presented higher discriminative indices, showing that more salient stimuli apparently control more observation responses. and consequently, exercise greater discriminatory control. Understanding the variations related to the problem-solving repertoire makes it possible to reduce learning time and establish discriminations, a factor that can expand learning possibilities